Weed behaviour in rainy-season onion (Allium cepa) as influenced by various weed-free and weedy treatments - SINGH, M P; SINGH, K P (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during 1988 and 1989 to study the weed behaviour in rainy-season (Kharif) Agrifound Dark Red' onion (Allium cepa L,) as influenced by various weed-free and weedy treatments. Fourteen were evaluated in randomized block design with 3 replications, viz weedy up to 15,30,45,60,75,90 days after transplanting and up to harvest and weed-free up to 15,30,45,60,75,90 days after transplanting and up to harvest. The total weed intensity and their dry weights were highest in weedy treatment up to harvest and least in weed-free treatment up to harvest. the monocol weeds were found more (in number) than dicor weeds. The N content in weeds increased with increase in weed-free period whereas its uptake showed the reverse trend.